Highly selective and sensitive fluorescence probe based on thymine-modified carbon dots for Hg2+ and l-cysteine detection. Issue 108 (20th October 2015) - Xu, Hui; Huang, Shanshan; Liao, Caiyun; Li, Yang; Zheng, Baozhan; Du, Juan; Xiao, Dan
Abstract : The as-prepared thymine-modified carbon dots were applied to as a sensor for detecting Hg 2+ andl -cysteine with high sensitivity and selectivity. Abstract : Herein, an "on–off–on" fluorescence probe for mercury ions andl -cysteine was designed and fabricated with thymine (T) covalently modified on the surface of carbon dots (CDs) by a simple, economical and effective strategy. The prepared thymine-coated CDs (CDs-T) could detect Hg 2+ ions with good selectivity and sensitivity by forming the specific thymine–Hg 2+ –thymine (T–Hg 2+ –T) structure, which induced aggregation of CDs-T and resulted in significant decrease of CDs's fluorescence intensity (on–off). In the presence ofl -Cys, the fluorescence was obviously recovered as the result of the disaggregation of CDs-T (off–on). In this process, Hg 2+ ions were removed from the comparatively weaker connected complex of T–Hg 2+ –T by the formation of stronger Hg 2+ –S bond between Hg 2+ andl -Cys, thus the aggregates were broken and the fluorescence could be turned on. Under the optimal conditions, the concentration linear range for detecting Hg 2+ andl -Cys were 0.03–8 μM ( R 2 = 0.9978) and 0.003–7 μM ( R 2 = 0.9957), respectively. The limits of detection (LOD) were as low as 0.93 nM and 0.88 nM, respectively. This method was successfully used to analyze Hg 2+ ions in real water samples and determinel -Cys in human urine and blood serum samples.